Beberapa Aspek Kependudukan yang Mempengaruhi Pernikahan di Bawah Umur - Najib Najib (Universitas Ngudi Waluyo, 2019)
Early marriage cases in Central Java were among the highest, reaching 3.876 in 2016. There is still a lot of value in young marriages generally triggered by economic problems and pregnancy outside of marriage. Early marriage allegedly contributed to the average TFR rate. No matter what needs to be done, a more in-depth analysis of various aspects related to things in age and distillation needs to be done early. This research is a qualitative analysis study using the LH Green Theory by only looking at the factors of Activation and Strengthening. Variables that pay attention to family support, the role of health workers, KUA officers, TOMA, culture and community values. The reasons are: Early Marriage Actors, Village Midwives, KUA Officers, Health Cadres and TOMAs who are members of the Village Health Forum, which are Interview Guidelines and Observation Guidelines. Descriptive data analysis with a qualitative approach was carried out by content analysis. The results showed that early marriage occurred for fear of being considered unsold, seeing the style of dating a teenager who could have sexual relations that resulted in pregnancy, so that it could embarrass their parents. Even though the teenager is not yet well established at work, it will be borne by the family. Low education for both parents and adolescents also encourages early marriage. The role of KUA officers and health workers has not been maximized in providing counseling related to reproductive health. The role of KUA officers is not maximal in related health, Parents are very supportive if inc married at the age of <20 years.